2014
DOI: 10.1371/journal.pone.0110722
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Mesenchymal Stem Cells and Effects on Neuronal Survival and Axon Regeneration after Optic Nerve Crush and Cell Therapy

Abstract: Bone marrow-derived cells have been used in different animal models of neurological diseases. We investigated the therapeutic potential of mesenchymal stem cells (MSC) injected into the vitreous body in a model of optic nerve injury. Adult (3–5 months old) Lister Hooded rats underwent unilateral optic nerve crush followed by injection of MSC or the vehicle into the vitreous body. Before they were injected, MSC were labeled with a fluorescent dye or with superparamagnetic iron oxide nanoparticles, which allowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 109 publications
5
88
1
1
Order By: Relevance
“…The cells were transplanted intramyocardially, and labeled cells could be effectively imaged and tracked by MRI for up to 40 days. 60 Besides those produced for clinical applications, several chemical companies also supply nonclinically approved SPIONs with different size ranges, coatings, and surface functionalities, as recently reviewed by Wang et al 56 Our group has also used a nonclinically approved nanoparticle, FeraTrack (Miltenyi Biotec), to label and track bone marrow-derived mononuclear cells 61,62 and mesenchymal stem cells 63 in different preclinical models of neurologic diseases. We were able to track labeled mononuclear cells after intravitreal injection in a rat model of optic-nerve crush, but 14 days post injection the signal derived from the transplanted cells was almost absent.…”
Section: Labeling Of Cells With Spionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cells were transplanted intramyocardially, and labeled cells could be effectively imaged and tracked by MRI for up to 40 days. 60 Besides those produced for clinical applications, several chemical companies also supply nonclinically approved SPIONs with different size ranges, coatings, and surface functionalities, as recently reviewed by Wang et al 56 Our group has also used a nonclinically approved nanoparticle, FeraTrack (Miltenyi Biotec), to label and track bone marrow-derived mononuclear cells 61,62 and mesenchymal stem cells 63 in different preclinical models of neurologic diseases. We were able to track labeled mononuclear cells after intravitreal injection in a rat model of optic-nerve crush, but 14 days post injection the signal derived from the transplanted cells was almost absent.…”
Section: Labeling Of Cells With Spionsmentioning
confidence: 99%
“…Immunostaining with the antibody anti-Iba1 revealed that the vast majority of the cells found in the vitreous body were negative for Iba1. 63 Recently, Ngen et al proposed and validated a method of dual-contrast with SPIONs and gadolinium chelate. …”
Section: Labeling Of Cells With Spionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of lipid vacuoles in differentiated adipocytes was evaluated by Oil Red O staining. Osteogenic differentiation and chondrogenic differentiation of WJ-MSCs were performed as previously described [20]. Osteogenic differentiation was demonstrated by calcium deposition in culture with Alizarin Red staining.…”
Section: Tri-lineage Mesenchymal Differentiationmentioning
confidence: 99%